2000
DOI: 10.1152/ajpcell.2000.279.6.c1993
|View full text |Cite
|
Sign up to set email alerts
|

Activation of pancreatic acinar cells on isolation from tissue: cytokine upregulation via p38 MAP kinase

Abstract: Cytokines produced by pancreatic acinar cells may mediate cell death and recruitment of inflammatory cells into pancreas in pancreatitis and other disorders. Here, we demonstrate mRNA expression for a number of cytokines in acini isolated from rat pancreas. Using RNA from microscopically selected individual cells, we confirmed the acinar cell as a source for cytokine expression. Competitive RT-PCR, Western blot analysis, and immunocytochemistry showed large amounts of monocyte chemotactic protein-1 and interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 41 publications
3
97
0
1
Order By: Relevance
“…However, it remains unclear which cells are secreting IL-6 in the pancreas. Recently, pancreatic acinar cells isolated from rodent were shown to express IL-6 (33). To the best of our knowledge, this study is the first report to demonstrate one of the local biosynthetic sites for IL-6 in human pancreas.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, it remains unclear which cells are secreting IL-6 in the pancreas. Recently, pancreatic acinar cells isolated from rodent were shown to express IL-6 (33). To the best of our knowledge, this study is the first report to demonstrate one of the local biosynthetic sites for IL-6 in human pancreas.…”
Section: Discussionmentioning
confidence: 55%
“…In various cells, the MAPK family has been shown to play an important role in regulating gene expression in response to inflammatory mediators (33). However, it has not fully been studied whether MAPKs participate in IL-17 signaling.…”
Section: Il-17 Il-1␤ and Tnf-␣ Induce The Activation Of Mapksmentioning
confidence: 99%
“…An in-vitro experiment showed that cytokine expression of acinar cells was mediated by two separate signal pathways, i.e, NF-κB and p38 MAP kinase. of which p38 MAP kinase is now suggested to play a major role [22][23][24][25][26][27] . The definitive role of these intracellular signaling cascades may lead to new designs for cytokine modulation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cascade of events during pancreatic cell isolation that may cause ␤-cell dysfunction and death is not fully characterized, recent lines of research in rodents (11,12) and humans (13) have indicated that oxidative stress plays a major role in triggering the death of islets and surrounding exocrine tissue. Other reports have demonstrated that oxidative stress is strongly connected to the adverse effects of chronic hyperglycemia on insulin biosynthesis by islet ␤-cells (14 -16).…”
mentioning
confidence: 99%